CO Dissociation Induced by 1 keV/u Ar2+ Ion - Zhang, Chijun; Zhang, Ruitian; Zhang, Shaofeng; Ma, Xinwen (Atoms, 2024)
CO is one of the important molecules in dense molecular clouds, and its dissociation induced by cosmic ray heavy ions is a fundamental process for molecular breaking up and rearrangement in astronomical networks. Extensive laboratory simulations are required to understand molecular evolution in astrophysical contexts. Here, we investigate the CO dissociation induced by 1 keV/u Ar2+ using cold target recoil ion momentum spectroscopy. Kinetic energy release for double electron capture Ar2++CO→Ar0+C++O+ and transfer ionization Ar2++CO→Ar++C++O++e− was obtained. The dissociation mechanisms are attributed to different KER distributions. The autoionization process is identified below the CO2+ double ionization threshold.